Preferred Internet Content and Social Anxiety as Drivers of Internet Addiction in Teens and Students - Kazarinova E.Yu; Kholmogorova A.B (Moscow State University of Psychology and Education, 2021)
The article presents the results of studying the connection between Internet addiction and social anxiety and the preferred types of Internet content among adolescents and young people studying in schools and universities. The sample consisted of 72 high school students of a secondary comprehensive school in Moscow aged 15 to 17 years (M=16), including 36 boys and 36 girls, as well as 72 junior students of Moscow universities aged 18 to 20 years old (M=19), of which 36 were boys and 36 were girls. The methodological complex included an Internet Addiction Test (K. Young), the original author's questionnaire of preferred Internet content, Social Avoidance and Distress Scale (SADS, Watson, Friend, 1969), Brief Fear of Negative Evaluation Scale (BFNE, Leary, 1983). It was revealed that the indicators of Internet addiction at the tendency level are higher in adolescents compared to students. Of the three components of social anxiety (social avoidance, social distress and fear of negative social assessment), only the indicator of fear of negative social assessment has a significant positive effect on the growth of indicators of Internet addiction in the combined group of respondents. The preference for content related to communication and self-presentation also has a significant impact on the growth of Internet addiction rates. Being overly concerned with other people's evaluations, seeking their approval, and focusing on self-presentation and social media communication all contribute to Internet addiction (increased time spent on the Internet, loss of control over it, as well as cognitive preoccupation with what is happening on the Internet).